COMPARATIVE STUDY ON SINGLE- AND DOUBLE-PASS CONFIGURATIONS FOR SERIAL DUAL-STAGE HIGH CONCENTRATION EDFA - Abdul Latiff, Anas; Zakaria, Zahriladha; Jaafar, Anuar; Abdul Rahim, Hazli Rafis; Gannapathy, Vigneswara Rao (IJRET, 2013)
A comparative study on a single- and double-pass configurations for Erbium-doped fiber amplifier (EDFA) are demonstrated using a gain media of high concentration Silica-based erbium doped fiber (EDF). The amplifier has two stages comprising a 1.5 m and 9 m long EDF optimized for C-band and L-band operations respectively, in a single-pass and double-pass configuration s. The CFBG is used at the end of EDF stage to allow a double propagation of signal and thus increases the attainable gain in both C- and L-band spectra. At an input signal power of -30 dBm, a flat gain of 22 dB is achieved with a gain variation of ±3 dB within a wide wavelength range from 1530 to 1600nm (C- and L-band) in double-pass configurations. The corresponding noise figure varies from 4 to 8 dB within this wavelength region. The flat gains for single-pass configuration only amplify within 1555 nm to 1600 nm (L-band).